2016
DOI: 10.1016/j.ultsonch.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Fast synthesize ZnO quantum dots via ultrasonic method

Abstract: Green emission ZnO quantum dots were synthesized by an ultrasonic sol-gel method. The ZnO quantum dots were synthesized in various ultrasonic temperature and time. Photoluminescence properties of these ZnO quantum dots were measured. Time-resolved photoluminescence decay spectra were also taken to discover the change of defects amount during the reaction. Both ultrasonic temperature and time could affect the type and amount of defects in ZnO quantum dots. Total defects of ZnO quantum dots decreased with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…The obtained results qualitatively agree with the experimental data of work [19]. Namely, it was found that the ultrasonic treatment of semiconductor quantum dots for 5-90 min in the course of their synthesis allows one to obtain nanoclusters that are more uniform by dimensions.…”
Section: Results Of Numericalsupporting
confidence: 87%
“…The obtained results qualitatively agree with the experimental data of work [19]. Namely, it was found that the ultrasonic treatment of semiconductor quantum dots for 5-90 min in the course of their synthesis allows one to obtain nanoclusters that are more uniform by dimensions.…”
Section: Results Of Numericalsupporting
confidence: 87%
“…Zn 1Àx Sn x O QDs were obtained aer continuous ultrasonication (ultrasonic frequency ¼ 53 kHz, ultrasonic power ¼ 180 W) to promote the reaction at 40 C for 30 min. Then, 0.6 mL of oleic acid (OA) 14,15 was used to precipitate the QDs. The white sediment was centrifuged for 5 min at 4000 rpm for 2-3 times and then washed with excess ethanol to remove any unreacted material.…”
Section: Synthesis Of Zn 1àx(y) Sn X(y) O Qds By Ultrasonic Methodsmentioning
confidence: 99%
“…Several methods have already been developed to synthesise ZnO (powder or thin lms), especially to control its morphology and porous texture, mainly by the following processes: chemical vapor deposition, 24 radio frequency magnetron sputtering, 25 spray pyrolysis, 26 molecular beam epitaxy, 27 pulse laser deposition, 28 atomic layer deposition, 29 hybrid-vapor phase epitaxy, 30 metal-organic vapor phase epitaxy, 31 vapor-phase synthesis, 32 synthesis from the melt, 33 hydrothermal synthesis, 34 precipitation, 35 co-precipitation, 36 and sol-gel 37 and sol-gel assisted ultrasonic methods. 38 In line with this, several morphological forms of zinc oxide including nanorods, nanotubes, hollow structures, nanocubes, ower-like structures, and nanospheres were prepared. 39 Ungula et al have synthesized ZnO nanoparticles via a sol-gel mineralization process using a sol-gel method with a systematic characterization by several analytical techniques to investigate the effect of the volume ratio of water versus ethanol on the structural, morphological and optical properties of ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 94%